Spatiotemporal characterization of microdamage accumulation and its targeted remodeling mechanisms in diabetic fatigued bone. Issue 2 (18th December 2019) - Liu, Xiyu; Li, Wei; Cai, Jing; Yan, Zedong; Shao, Xi; Xie, Kangning; Guo, X. Edward; Luo, Erping; Jing, Da
Abstract: The skeleton of type 1 diabetes mellitus (T1DM) has deteriorated mechanical integrity and increased fragility, whereas the mechanisms are not fully understood. Load‐induced microdamage naturally occurs in bone matrix and can be removed by initiating endogenous targeted bone remodeling. However, the microdamage accumulation in diabetic skeleton and the corresponding bone remodeling mechanisms remain poorly understood. Herein, streptozotocin‐induced T1DM rats and age‐matched non‐diabetic rats were subjected to daily uniaxial ulnar loading for 1, 4, 7, and 10 days, respectively. The SPECT/CT and basic fuchsin staining revealed significant higher‐density spatial accumulation of linear and diffuse microdamage in diabetic ulnae than non‐diabetic ulnae. Linear microcracks increased within 10‐day loading in diabetic bone, whereas peaked at Day 7 in non‐diabetic bone. Moreover, diabetic fatigued ulnae had more severe disruptions of osteocyte canaliculi around linear microcracks. Immunostaining results revealed that diabetes impaired targeted remodeling in fatigued bone at every key stage, including increased apoptosis of bystander osteocytes, decreased RANKL secretion, reduced osteoclast recruitment and bone resorption, and impaired osteoblast‐mediated bone formation. This study characterizes microdamage accumulation and abnormal remodeling mechanisms in the diabetic skeleton, which advances our etiologic understanding of diabetic bone deterioration and increased fragility from the aspect of microdamage accumulation and bone remodeling.